Behavior of Ball Penetrometer in Nonhomogeneous Clay in Centrifuge Test - Yuanting Xiong; Yongle Qi; Sen Zhang; Xiaobin Ding; Shuyi Li; Mi Zhou (Advances in Civil Engineering)
Ball penetrometers have been employed in both centrifuge tests and field experiments for soil profile interpolation. Nevertheless, it has become apparent that the performance of the ball penetrometer in centrifuge tests significantly deviates from that in field tests. In this study, a more comprehensive analysis utilizing the larger deformation finite element method was undertaken to gain deeper insights into the behavior of ball penetrometers when used in nonhomogeneous clay within the centrifuge testing environment. This investigation accounts for the influence of the unique scale and shaft ratio of the ball penetrometer in centrifuge tests. The numerical model developed in this study was rigorously validated against previously published data, demonstrating a high degree of agreement. Subsequently, a parametric study was conducted to investigate potential influencing factors. As a result, a novel method for quantifying the bearing capacity factor was proposed. This method offers the promise of obtaining more precise data regarding the continuous shear strength in centrifuge tests, thereby providing valuable guidance for soil profile determination within this experimental setting.